Reproducibility of shear wave elastography (SWE) in patients with chronic liver disease - Mancini, Marcello; Salomone Megna, Angelo; Ragucci, Monica; De Luca, Massimo; Marino Marsilia, Giuseppina; Nardone, Gerardo; Coccoli, Pietro; Prinster, Anna; Mannelli, Lorenzo; Vergara, Emilia; Monti, Serena; Liuzzi, Raffaele; et al. (PloS one, 2017)
The presence of significant fibrosis is an indicator for liver disease staging and prognosis. The aim of the study was to determine reproducibility of real-time shear wave elastography using a hepatic biopsy as the reference standard to identify patients with chronic liver disease. Forty patients with chronic liver disease and 12 normal subjects received shear wave elastography performed by skilled operators. Interoperator reproducibility was studied in 29 patients. Fibrosis was evaluated using the Metavir score. The median and range shear wave elastography values in chronic liver disease subjects were 6.15 kPa and 3.14-16.7 kPa and were 4.49 kPa and 2.92-7.32 kPa in normal subjects, respectively. With respect to fibrosis detected by liver biopsy, shear wave elastography did not change significantly between F0 and F1 (p = 0.334), F1 and F2 (p = 0.611), or F3 and F4 (0.327); a significant difference was observed between the F0-F2 and F3-F4 groups (p = 0.002). SWE also correlated with inflammatory activity (Rs = 0.443, p = 0.0023) and ALT levels (Rs = 0.287, p = 0.0804). Age, sex and body mass index did not affect shear wave elastography measurements. Using receiver operator characteristic curves, two threshold values for shear wave elastography were identified: 5.62 kPa for patients with fibrosis (≥F2; sensitivity 80%, specificity 69.4%, and accuracy 77%) and 7.04 kPa for patients with severe fibrosis (≥F3; sensitivity 88.9%, specificity 81%, and accuracy 89%). Overall interobserver agreement was excellent and was analysed using an interclass correlation coefficient (0.94; CI 0.87-0.97).This study shows that shear wave elastography executed by skilled operators can be performed on almost all chronic liver disease patients with high reproducibility. It is not influenced by age, sex or body mass index, identifies severely fibrotic patients and is also related to inflammatory activity.